USING MANAGEMENT CONTROL TO ALIGN ORGANIZATIONAL STARTEGIES AND TO MEASURE PERFORMANCES - VOLKAN ILDIKO REKA (Annals of the University of Oradea: Economic Science, 2009)
Practice shows that, in order to improve internal and external communication, managers need to increase the request of information about their business administration. So, for this, they need a complementary system which assures them this kind of informat